Filosofía y cosmovisión andina en el proceso sancionatorio de la justicia indígena en el Ecuador. - Molina, Cristian B. (2022)
By means of this work, it is intended to generate a legal-philosophical analysis of the Andean worldview and its incidence within the sanctioning process of Indigenous Justice in Ecuador, within the framework of legal pluralism and the constitutionalization of criminal law, under the umbrella of the due process guarantees. It also seeks to analyze and compare the dogmatic precepts of the worldview of the Andean peoples, with the philosophical principles of Western criminal law and its incidence within Ecuadorian constitutional law, in order to establish a referential framework and conceptual guide that allows clarifying the scope and procedures for the application of indigenous justice and compliance with the constitutional guarantees of Due Process. By philosophically comparing the dogmatic precepts of the Andean worldview and the philosophy of Western law within the sanctioning procedure, it will be possible to identify the phases of the sanctioning process of Indigenous Justice in Ecuador to establish the relationship of similarities and differences between the philosophy of positive law with the Andean worldview applied in the sanctioning process in the exercise of indigenous justice. The scope of this investigation will allow to establish a legal criterion that serves as a referential element and guide to leaders of indigenous communities in the scope of the procedure of application of indigenous justice and the fulfillment of the constitutional guarantees of due process within the phases of the process sanctioning, contributing to the construction of a legal pluralism with a guaranteeing approach to fundamental rights.